(untitled) (Proceedings of International Conference on Special Education, 2017)
The purposes of the study is to do research on the problems faced by the Institution Administration for Visually Impaired. There are 5 groups working, Academic Administration, Personnel Administration, Fiscal Administration, General Administration and Student Affairs Administration. The educational information is given by the school for the Visually Impaired. The grouping interview is chosen and the specialist is chosen by using the semi-structure interviewing, Data Analysis been has done by using the content analysis. The results are: Academic Administration-Teaching activities are non-variety pattern, Evolution 1) process is not agreement with the students’ handicap media needs more modernity styles 2) Personnel Administration- Teachers and education officers are not specialized in the subject contents and the necessary skills for the visually impaired, school also needs more teachers to be suitable with the government criterion. 3) Planning and Fiscal Administration: The Government’s budgets do not show the reflection of the exactly educational expenses. Besides the costs of teaching technology are also expensive and requested from the foreign countries. 4) The General Administration needs more offensive public relations to the parent government and social community. The School realized the important of education and having a good attitude for the potential acceptation of the visually impaired. The opportunity for studying needs to concern more than sympathizes from their handicap. The personnel information system of the visually impaired overall of Thailand need to create the connection and the integrative between the educational government and develop the quality of life to reach the right of elementary level and an appropriately opportunity. 5) The student Administration-The farther shelters and poor family are the problem to cooperate for developing the student’s quality of life property.